PELATIHAN PENGELOLAAN KEUANGAN KELUARGA PADA IBU-IBU DI KECAMATAN LUBUK PAKAM - Irna Triannur Lubis; Etty Harya Ningsi; Lambok Manurung (Nusantara Hasana Journal, 2024)
Family financial management is an essential skill that directly contributes to household welfare, especially among housewives who act as family financial managers. This community service activity aims to improve the literacy and skills of mothers in Lubuk Pakam District in managing family finances wisely and sustainably. The implementation methods include participatory education, direct training, and simple household financial recording simulations carried out interactively. The results of the activity showed a significant increase in participants' understanding of the basic concepts of financial management, including budgeting, recording expenses, and savings planning. In addition, this training succeeded in encouraging changes in financial behavior towards a more rational and planned direction. This activity proves that financial literacy-based empowerment has great potential in supporting family economic resilience at the community level. The implications of this activity can be used as a model for similar interventions in other areas with comparable socio-economic characteristics.